ASPEK HUKUM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) BIDANG KETENAGAKERJAAN DALAM PERSPEKTIF SISTEM JAMINAN SOSIAL NASIONAL - Suhardi Suhardi (VERITAS, 2016)
Legal Aspects of Social Security Agency (BPJS) in the field of employment in theperspective of national social security system in order to improve the welfare of thecommunity is very clear, it is seen from the implementation of the Law on National SocialSecurity System (Social Security Act) and the Law on Social Security Agency (BPJS) bothby governments and society in general. The government of which has made theimplementation provisions of the Act mentioned above, also have to continuously executeall commands such legislation. From the second application of the law is seen thatparticipants in the National Social Security System Social Security Agency conducted everyyear has increased. Thus it can be said that the Government succeeded in organizingnational social security system in the public welfare.